PENINGKATAN KETERAMPILAN MENULIS ARGUMENTATIF MELALUI MODEL HALAQAH : Studi Pengembangan Model Pembelajaran dan Kepribadian Menulis pada Siswa Kelas X SMA Kartika Kendari - Amirudin, - (2011)
he title of this disertation is The Increasing of an Argumentative Writing Skill by Using the Halaqah Model: The Development Study of Teaching and Learning and Personality of Writing for the 10th Grade Students of SMA Kartika Kendari. The research background based on the issues and the results of literature research study shown that the writing skill of some subjects study (students and undergraduate students) lower and especially for the argumentative writing skills difficult. It brings to find out the alternative ways, to cope the difficulties and the lowerity of writing skill. The Model Halaqah Ilmiah (MHI) is an alternative way in this study. The experimental design with randomized pretest-postest comparison group design is used as a method. A qualitative analysis used for the data of argumentative writing students, a questionnaire, an interview, and observation. And SPSS program version 17 used for analysing of the quantitative data from the pre-test and post-test from model halaqah ilmiah (MHI), model halaqah tradisional (MHT), and model konvensional (MKonv.) The result of this study proved that MHI could increase the student argumentative writing skill. Which the significance value of MHI on the table is 0.00 < α 0.05 based on an analysis of varian covarian with MHT and MKonv. And refer to the difference of averages and the increasing gain shown that MHI result better than MHT and MKonv. This study presents that (1) MHI as a new model on the teaching and learning of an argumentative writing in the senior high school have a possitive contribution in the increasing of the students argumentative writing skill, (2) the process of teaching and learning of halaqah model has created the context of teaching and learning more comfortable, dinamic, egaliter, and democratic in the familliarity , brotherhood, and unity situations, and naturally the students more active with the process of rolling activity in the halaqah; (3) MHI could the writing personalities, humble, familiarity, and critic. The quality of MHI will be better when the teacher mentions the subject matter in detail then it brings to harmonization between the increasing of the basic knowledge and the argumentative writing skill and also important to have a balancing activities between intrahalaqah and suprahalaqah.